NABH Accreditation and its status in the Country - Vivek Hittinahalli; Saroj Golia (Al Ameen Medical College, 2013)
National Accreditation board for hospitals and healthcare providers (NABH) is a national body responsible for providing accreditation to the hospitals. General accreditation programs appear to improve the structure and process of care, with a good body of evidence showing that accreditation programs improve clinical outcomes. General accreditation programs of health organizations and accreditation of subspecialties should be encouraged and supported to improve the quality of healthcare services]. One of the most important barriers to the implementation of accreditation programs is the skepticism of healthcare professionals in general and physicians in particular about the positive impact of accreditation programs on the quality of healthcare services. However with quality in healthcare an important aspect, healthcare accreditation has become a most important tool for improving the standard of the hospitals and thereafter benchmarking